AUTOMATION OF THE PROCESS OF MONITORING THE PARAMETERS OF INTERBLOCK ELECTRICAL CONNECTIONS - BUKOVSKY, OLEG; VYSLOUKH, SERGEI (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The utilization of traditional automated systems and industrial robots is typically restricted to environments that are well-structured. These systems often lack the ability to effectively handle complexity and uncertainty, resulting in limited adaptability. As a result, their application in small and medium-sized enterprises is constrained. The automated system for monitoring the parameters of interconnection connections based on adaptive algorithms is an innovative approach aimed at improving the productivity of production and reliability of cable and wire products. Within the framework of this work, an analysis of the existing methods for monitoring the parameters of interblock electrical connections was carried out, which made it possible to identify their features and shortcomings. This analysis highlighted the need to develop new approaches to control these parameters using adaptive algorithms. In the context of this problem, the use of adaptive algorithms provides the system with the ability to minimize the error rate of signal reproduction. This helps to increase the accuracy and reliability of the control process, as the system is able to respond to unforeseen situations and correct its work in real time. In addition, the key element of this work is the development of a block diagram of a modular type of control system. This scheme provides flexibility and scalability of the solution, since each module of the system is responsible for a specific aspect of controlling the parameters of interconnection connections. This approach simplifies the management and maintenance of the system, as well as makes it more accessible for implementation in a variety of industries. The results of this study testify to the relevance of the problem of controlling the parameters of interblock electrical connections and confirm the prospects of using an automated control system with adaptive algorithms. The use of such a system can significantly increase the productivity of production and reliability of products used in the fields of instrumentation and mechanical engineering.